If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + -1(-41) = 0 Multiply -1 * -41 25 + 41 = 0 Combine like terms: 25 + 41 = 66 66 = 0 Solving 66 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| x^2(x^2)-16(x^2-1)=0 | | -29-6x=-5(-5x+1)-7x | | Sinx=3 | | 2b+58b=35 | | -21+5+-9=3(t-4)-5 | | 71=6(4n-8)-7n | | 2(x-5)=3(x-1) | | s+6=78 | | 2x+3y-5x+5y= | | 5(1+6a)=-39+8a | | 2+2v=-2 | | 2z^3+9z^2=5z | | 5b-16-8n=-10 | | 7(y+1)=49 | | K=17 | | X+3=-32 | | 15-f=-23 | | 4-5(x+3)=25 | | -22+7r=6(r-4) | | 3x+7+6x+11=90 | | 4x+1=11x | | -2(5y+5)=4 | | 3*x=10 | | 8+16=-3(5x-8) | | 9(6x-5)=279 | | 22x-16x+12=-15+3x+12+6x | | 5x-9=13-x | | 7=20 | | 120*24= | | -30+5n=4+4(1+6n) | | -4(x+8)=-3x-5 | | 4(y+5)=-6(2y-1)+4y |